Commitment to the study of international business and cultural intelligence - Abi Aad, Amine (2014)
Adopting a multilevel theoretical framework, we examined how metacognitive and motivational cultural intelligence influence an individual’s commitment to the study of international business (IB). Data from 292 undergraduate and graduate business students nested in 12 U.S. business school classes demonstrated that individuals’ metacognitive and motivational cultural intelligence are positively related to their commitment to the study of IB. Furthermore, there is additional commitment when the classrooms’ cultural intelligence climate is high. We discuss the implications of these findings within a classroom context that involves cross-cultural interactions.